2008
DOI: 10.2320/matertrans.mra2008167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Resonant Characteristics of Friction Stirred AZ31-Mg Alloy

Abstract: An annealed AZ31-Mg specimen (AZ31-O) was given a FSP (friction stir process) to obtain a AZ31-FSP specimen, whose tensile and vibration fracture mechanisms are examined in this study. As a result of FSP, the structure of the stirred zone (SZ) separated into two zones: (1) the SZ-top had a finer structure and (2) the grain size of the SZ-bottom was like the AZ31-O specimen. Because the basal plane (0002) had pressed close to the trace surface of the onion structure in the SZ, the recrystallization of FSP incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The center of stir zone (SZ) revealed that the network-like structure (dynamic recrystallization and texture effect) 7) and the particle-like structure (frictional heat of shoulder) 8,9) were found from the thermo-mechanically affected zone (TMAZ) of advancing side to bottom of stir zone.…”
Section: Resultsmentioning
confidence: 99%
“…The center of stir zone (SZ) revealed that the network-like structure (dynamic recrystallization and texture effect) 7) and the particle-like structure (frictional heat of shoulder) 8,9) were found from the thermo-mechanically affected zone (TMAZ) of advancing side to bottom of stir zone.…”
Section: Resultsmentioning
confidence: 99%
“…By virtue of the through-thickness dual gradients, the best strength-ductility combination of AZ31 sheets was obtained using SRR technique with P = 200 N, as shown in Figure 5, compared to its counterparts by various deformation processes, including homogeneous refinement and SMAT. [23,25,29,31,[35][36][37] It is noted that the SRR-treated sample with the optimal mechanical performance exhibits the dual gradients in the whole sample (about 0.9 mm) but no over hardening, compared to the case when P = 280 N.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with the other thin films, 17) the matrix of the evaporating Mg-10Li thin film was uniform and had no voids. According to electrodes references, 18,19) the annealing would increase the uniformity of thin film, so the charge-discharge experiment of annealed Mg-10Li thin film was performed at room temperature. Figure 8 shows the curve of charge-discharge capacity for annealed Mg-10Li alloy film, which takes the first cycle as the basic value (380 mAh/g).…”
Section: Resultsmentioning
confidence: 99%